L’histoire des populations maritimes à l’époque contemporaine : la géographie au service de l’historien. - Nicolas Cochard (EchoGéo)
In the context of research in the field of current maritime history, we are considering the part played by geographic contributions in the works on the history of sea people. This study thus underlines the necessity to make the two human sciences interact in this field of research so as to get an accurate perception of how sea people have marked space and the society.